Investigation on the synergistic effect of γ-aminopropyltriethoxysilane and polyethylene-grafted glycidylmethacrylate on the properties of high-density polyethylene/poplar wood flour composites and their synergistic mechanism. (March 2017) - Ding, Yunsheng; Ni, Guozhang; Xu, Pei; Ali, Bahader; Yang, Shanzhong
Wood–plastic composites were prepared from poplar wood flour and high-density polyethylene (HDPE) by melt blending and injection molding techniques, using polyethylene-grafted glycidylmethacrylate (HDPE- g -GMA) as compatibilizer and γ -aminopropyltriethoxysilane as coupling agent. The scanning electron microscopy results showed that a stronger interfacial adhesion was formed between the wood flour and HDPE matrices during the combined use of γ -aminopropyltriethoxysilane and HDPE- g -GMA, while the X-ray photoelectron spectroscopy results showed that more HDPE chains are linked to the surface of poplar wood flour through the formation of chemical bonding in the presence of γ -aminopropyltriethoxysilane and HDPE- g -GMA. So, HDPE- g -GMA and γ -aminopropyltriethoxysilane showed a synergistic effect on the improvement of compatibility between the poplar wood flour and HDPE matrices and better mechanical properties of wood–plastic composites could be obtained. Furthermore, the thermogravimetric analysis results also indicated the synergistic effects to some extent. The synergistic mechanism of γ -aminopropyltriethoxysilane and HDPE- g -GMA was proposed on the basis of investigation results.